Executive's guide to cyber risk : securing the future today - Moyo, Siegfried (Wiley, 2022)
"This book offers any senior level executive an understanding of the core fundamentals of Cyber Risk, which is critical for any business to remain sustainable and viable in the information age era of disruptive cyber-attacks. For any executive to understand that Cyber Risk is like any other business risk, it needs to be explained in focused non-technical terms. The book provides core foundational precepts of cyber risk that will enable executive leadership to make well-informed decisions along with their senior cyber security executives regarding cyber risk management. In addition, describes the different approaches by executives to cyber risk. There are three types of executive leadership: (1) hindsight, (2) foresight, or (3) none of the two. This book shows how to be a cyber risk leader through foresight while maintaining the corporation's vision and objectives (proactive vs. reactive)"--